Psychometric performance of EQ-5D-5L and SF-6DV2 in measuring health status of populations in Chinese university staff and students - Hui Jun Zhou; Aixue Zhang; Jie Wei; Jing Wu; Nan Luo; Pei Wang (BMC, 2023)
Abstract Aims To compare measurement properties of EQ-5D-5L and SF-6DV2 in university staff and students in China. Methods A total of 291 staff and 183 undergraduates or postgraduates completed the two instruments assigned in a random order. The health utility scores (HUS) of EQ-5D-5L and SF-6DV2 were calculated using the respective value sets for Chinese populations. The agreement of HUSs was examined using intraclass correlation coefficients (ICC) and Bland-Altman plot. Convergent validity of their HUSs and similar dimensions were assessed using Spearman's correlation coefficient. Known-group validity of the HUSs and EQ-VAS score was assessed by comparing the scores of participants with and without three conditions (i.e., disease, symptom or discomfort, and injury), as well as number of any of the three conditions; their sensitivity was also compared. Results The ICCs between the two HUSs were 0.567 (staff) and 0.553 (students). Bland-Altman plot found that EQ-5D-5L HUSs were generally higher. Strong correlation was detected for two similar dimensions (pain/discomfort of EQ-5D-5L and pain of SF-6DV2; anxiety/depression of EQ-5D-5L and mental health of SF-6DV2) in both samples. The correlation between the two HUSs were strong (0.692 for staff and 0.703 for students), and were stronger than their correlations with EQ-VAS score. All the three scores could discriminate the difference in three known-groups (disease, symptom or discomfort, number of any of the three conditions). The two HUSs were more sensitive than EQ-VAS score; and either of them was not superior than the other. Conclusions Both EQ-5D-5L and SF-6DV2 HUSs have acceptable measurement properties (convergent validity, known-groups validity, sensitivity) in Chinese university staff and students. Nevetheless, only EQ-5D-5L (PD and AD) and SF-6DV2 (PN and MH) showed indicated good convergent validity as expected. Two types of HUSs cannot be used interchangeably, and each has its own advantages in sensitivity.